2019
DOI: 10.1177/2056305119855141
|View full text |Cite
|
Sign up to set email alerts
|

Social Media for Political Campaigns: An Examination of Trump’s and Clinton’s Frame Building and Its Effect on Audience Engagement

Abstract: This study investigates cross-platform differences in social media by analyzing the contending candidates who represent different political ideology during the 2016 presidential election. Borrowing the frame-building and frame-effect perspectives, it examines the ways in which the two contending candidates (Donald Trump and Hillary Clinton) built their message frames in two different social platforms-Twitter (N = 3,805) and Facebook (N = 655)-and how the frame differences affected audience engagement in each p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 60 publications
(106 reference statements)
1
23
0
1
Order By: Relevance
“…Prior research has confirmed emotion and rationality as twin engines of persuasion and responsiveness in online communication (X. Liu et al, 2019;Sahly et al, 2019). Emotional appeals are arousal-inducing features, which can increase social transmission of information (Berger, 2011).…”
Section: Emotion and Rationalitymentioning
confidence: 98%
“…Prior research has confirmed emotion and rationality as twin engines of persuasion and responsiveness in online communication (X. Liu et al, 2019;Sahly et al, 2019). Emotional appeals are arousal-inducing features, which can increase social transmission of information (Berger, 2011).…”
Section: Emotion and Rationalitymentioning
confidence: 98%
“…Investigations into the effects of engagement with, and exposure to, politicians' profiles for citizens remain scarce, with notable exceptions. Studies demonstrate that politicians' communication on social media can affect perceptions of a political actor's authenticity (Enli & Rosenberg, 2018;Kreiss et al, 2018) and audience engagement (e.g., Sahly et al, 2019). Kristensen et al (2017) find that voting intention can be linked to citizens 'liking' the representations of politicians on social media.…”
Section: Following Politicians and Campaign Mobilizationmentioning
confidence: 99%
“…Meanwhile, the digital environment adds in the ever-expanding role of online publics [26,27] who organically share a variety of information and conversations that intermixes news coverage, activist messages, memes, catchphrases, emotions, and both pro-and counter-protest opinions [27,28]. This is known as the process of "networked framing.…”
Section: Networked Framingmentioning
confidence: 99%